Effect Of Variation Barbiturate (Sodium Phenobarbitone) Lethal Dose On Calliphoridae Larvae Length To Rat (Rattus Norvegicus) Carcasses Wistar Strain - Dwi Astuti Wulandari; Syamsun, Arfi; Triani, Eva (Faculty of Medicine Universitas Mataram, 2020)
Background: Determining the time of death (post-mortem interval) is very important in forensic investigations. Blowflies growth is the main and most accurate indicators time of death to estimation PMI. The growth of flies can be affected by various factors including climate, geography, and medicines contained in the body. The aim of this study was to examine the effect of giving variations barbiturate (sodium phenobarbitone) lethal dose to the length of Calliphoridae larvae to predicting PMI. Methods: This study is an experimental study with post-test only control group design, the data were analyzed using multivariate linear regression analysis test. This study consisted of 1 control group (neck dislocation) and 3 control groups of phenobarbital (750 mg/kgBW, 900 mg/kgBW and 1050 mg/kgBW). All group are put into a cage containing Chrysomya sp. The measurements of larva length are carried out every 12 hours by taking the largest larvae size in each rat in the study group. Result: The results shown that phenobarbital was the most influential factor in the larval length of Chrysomya sp. (p <0.05, R = -0.64) compared to temperature and humidity. Mann Whitney test results (p <0.05) shown the significant difference in Chrysomya sp. larvae length in each study group. Conclusions: Variation lethal dosage of barbiturates (sodium phenobarbital) affects the growth of Chrysomya sp larvae length.